2014
DOI: 10.1097/jom.0000000000000287
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Individual PM2.5 Exposure and DNA Damage in Traffic Policemen

Abstract: These results demonstrated that traffic policemen have been a high-risk group suffering DNA damage because of the high PM2.5 exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In fact, these mechanisms may interact to contribute to teratogenesis. For example, certain air pollutants (e.g., PM 2.5 ) could lead to genetic toxicity by forming DNA adducts (Li et al, 2014). These adducts are mutagenic, resulting in the disruption of the cell's microenvironment, which leads to inhibition of important enzymes, cell death, and alteration of other cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these mechanisms may interact to contribute to teratogenesis. For example, certain air pollutants (e.g., PM 2.5 ) could lead to genetic toxicity by forming DNA adducts (Li et al, 2014). These adducts are mutagenic, resulting in the disruption of the cell's microenvironment, which leads to inhibition of important enzymes, cell death, and alteration of other cells.…”
Section: Discussionmentioning
confidence: 99%
“…People who work in spaces with high PM exposure (e.g., traffic attendants, street repair workers, bus drivers, etc.) may have greater exposures and thus may have increased vulnerability to PM 2.5 -induced health consequences (Han et al, 2005; Li et al, 2014). Further, the link between PM exposure and olfactory loss stresses the need for additional research into the health effects of air pollutants beyond the focus of conventional studies to date (heart, lung, and brain disease primarily), especially for sensory systems.…”
Section: Discussionmentioning
confidence: 99%
“…The nematode of Caenorhabditis elegans (C. elegans), a non-mammalian model, has been widely used for biomedical and environmental toxicity evaluation because of its short lifespan, high reproduction rate, simple nervous system, adequately described genetics, high level of molecular preservation, transparent body, inexpensive and convenient maintenance, sensitivity to environmental toxins, and without the animal ethics issues (Brenner, 1973;Kaletta and Hengartner, 2006a;Leung et al, 2008;Maurer et al, 2015;Hunt, 2017;Chung et al, 2019). However, not many published articles focused on C. elegans exposure to PM2.5 and the related adverse effects, especially TRAP PM2.5 (Zhao et al, 2014;Sun et al, 2015;Yang et al, 2015;Sun et al, 2016;Wu et al, 2017;Chung et al, 2019;Zhao et al, 2019;Chung et al, 2020b). Studies on adverse effects of TRAP PM2.5 in C. elegans models, found that TRAP PM2.5 caused reproductive and neurological toxicity and shortened the lifespan of nematodes after prolonged exposure to TRAP PM2.5 (Chung et al, 2020a).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…TRAP PM2.5 has large surface areas to be covered on several organic (i.e., polycyclic aromatic hydrocarbons) or inorganic (i.e., heavy metals) chemicals and some of them are toxic (Dadvand et al, 2015;Sram et al, 2017;Rahmatinia et al, 2021;Hao et al, 2022). TRAP PM2.5 may induce inflammatory responses (Chao et al, 2018), DNA adducts or damage (Li et al, 2014), and lung function deterioration in traffic conductors or policemen (Putri Anis Syahira et al,…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%